Ethanol Production from Molasses with Immobilized Cells Technique in Packed Bed Bioreactor by Extractive - Musfil AS; Tri Widjaja; Ali Altway; R. Darmawan Darmawan (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
The aim of this research was to study the effect of total sugar concentration, Ca-Alginate and K Carrageenan density in immobilized cells on packed-bed and batch bioreactor performance for ethanol production. In addition, this research was also aimed to study the effect of solvent flow rate on packed column performance expressed as % extraction recovery. This experiment was carried out with total sugar concentration of 10, 14, 18 % (v/v) and immobilized cells Ca-Alginate and K-Carrageenan at a density of 2% (w/v) with amyl alcohol as solvent. Based on the result of this study, it is concluded that the total sugar concentration influenced the concentration, yield and productivity of ethanol. The result of this study for immobilized Ca-Alginate cells showed that the maximum ethanol product concentration, yield and productivity were 7.28% g/l, 57.48 g/l, 38.22%, 71.85 g/l.hr, respectively. Meanwhile, immobilized K-Carrageenan cells showed the maximum ethanol product concentration, yield and productivity as 7.22% /56.99 g/l, 26.73%, and 68.40 g/l.hr, respectively. In extraction process, increasing amyl alcohol solvent flow rate will increase mass transfer and hence increase ethanol recovery.